Aspects of Mathematical Logic - Casari, E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
H. Hermes: Basic notions and applications of the theory of decidability.- D. Kurepa: On several continuum hypotheses.- A. Mostowski: Models of set theory.- A. Robinson: Problems and methods of model theory.- S. Sochor, B. Balcar: The general theory of semisets. Syntactic models of the set theory.
H. Hermes: Basic notions and applications of the theory of decidability -- D. Kurepa: On several continuum hypotheses -- A. Mostowski: Models of set theory -- A. Robinson: Problems and methods of model theory -- S. Sochor, B. Balcar: The general theory of semisets. Syntactic models of the set theory.
Keywords: Mathematics; Logic, Symbolic and mathematical; Mathematics; Mathematical Logic and Foundations